Determinan Kualitas Tidur Remaja Berdasarkan Teori Kognitif Sosial: Studi Literatur Tahun 2021-2025 - Tengku Siti Neza Azmarina; Luqman Effendi (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Sleep is a fundamental biological need for adolescents and plays a crucial role in supporting cognitive function, emotional regulation, and overall mental health. Despite its importance, sleep quality among adolescents has increasingly declined due to the interaction of individual characteristics, social environments, and daily sleep behaviors. This article aims to analyze the factors influencing adolescent sleep quality using the Social Cognitive Theory framework through a literature review of national and international journals published between 2021 and 2025. The findings show that adolescent sleep quality is shaped by personal factors, including attitudes toward sleep, self-efficacy, and psychological conditions. Environmental factors, such as parental support, peer influence, and academic demands, also significantly affect sleep patterns. In addition, behavioral factors, particularly sleep hygiene practices, play a key role in determining sleep quality. Consistently, unhealthy sleep behaviors are associated with poor sleep quality. Therefore, comprehensive interventions are needed, involving the improvement of sleep habits, strengthening adolescents’ self-regulation abilities, and enhancing family and school support to promote better sleep quality.